Detection of the rhlR Gene in Clinical Isolates of Pseudomonas aeruginosa Using Polymerase Chain Reaction (PCR) - Nova Dwi Sulistyawati; Didik Wahyudi (Laboratory Journal of Infectious Diseases, 2026)
Pseudomonas aeruginosa is an opportunistic bacterium capable of forming biofilms through quorum sensing mechanisms regulated by the rhlR gene. The presence of this gene contributes to bacterial virulence and enhanced antibiotic resistance. This study aimed to detect the rhlR gene in clinical isolates of P. aeruginosa obtained from sputum, urine, and pus samples using the Polymerase Chain Reaction (PCR) method. This descriptive laboratory-based study analyzed six clinical isolates of Pseudomonas aeruginosa. Identification of isolates was performed through Gram staining, culture on MacConkey agar, and biochemical tests. DNA isolation was carried out using the Presto™ Mini gDNA Bacteria Kit, followed by qualitative and quantitative DNA analysis. Amplification of the rhlR gene was performed using specific primers targeting a 133 bp amplicon. The results showed that all isolates produced adequate DNA concentrations ranging from 147–155 ng/µL with purity ratios ranging from 1,1–1,9. PCR amplification demonstrated the presence of positive bands at 133 bp in all samples, indicating the presence of the rhlR gene. In conclusion, the rhlR gene was successfully detected in all clinical isolates of Pseudomonas aeruginosa. These findings suggest that the isolates possess quorum sensing-related virulence potential associated with biofilm formation.